Using both electromyography and movement disorder assessment improved the classification of children with dyskinetic cerebral palsy. (11th November 2021) - Lorentzen, Jakob; Born, Alfred P.; Svane, Christian; Forman, Christian; Laursen, Bjarne; Langkilde, Annika R.; Uldall, Peter; Hoei‐Hansen, Christina E.
Abstract: Aim: Children with dyskinetic cerebral palsy (CP) are often severely affected and effective treatment is difficult, due to different underlying disease mechanisms. Comprehensive systematic movement disorder evaluations were carried out on patients with this disorder. Methods: Patients born from 1995 to 2007 were identified from the Danish Cerebral Palsy Register and referrals to the neuropaediatric centre, Rigshospitalet, Copenhagen. They were classified by gross motor function, manual functional ability, communication ability, dystonia and spasticity. Electromyography was carried out on the upper and lower limbs. Magnetic resonance imaging scans were revised, and aetiological searches for underlying genetic disorders were performed. Results: We investigated 25 patients with dyskinetic CP at a mean age of 11.7 years. Dystonia, spasticity and rigidity were found in the upper limbs of 21, four and six children, respectively, and in the lower limbs of 18, 18 and three children. The mean total Burke‐Fahn‐Marsden score for dystonia was 45.02, and the mean Disability Impairment Scale level was 38% for dystonia and 13% for choreoathetosis. Sustained electromyography activity was observed in 20/25 children. Stretching increased electromyography activity more in children with spasticity. There were 10 re‐classifications. Conclusion: The children had heterogenic characteristics, and 40% were reclassified after systematic movement disorder evaluation.